Future tourism trends. volume 2 : technology advancement, trends and innovations for the future in tourism - Tanrisever, Canan; Pamukçu, Hüseyin; Sharma, Anukrati (Emerald Publishing Limited, 2024)
The world is entering a new technological age in which great changes are expected in all areas of human interest, life, and activity. These changes have been brought on by past and present man-made events, which have had both positive and negative consequences. The coming millennium will be marked by significant social, political, demographic, and technological changes, and will definitely differ from the last century. The future will bring more leisure time, a higher standard of living, and a better quality of life for us all. Technology advancement, Trends and Innovations for the Future in Tourism examines recent and the most probable changes and answers questions such as: How will AI, service robots, and voice control affect tourism? Is this new era transforming the very essence of travelling? The authors present a wide range of visionary insights, as well as operational takeaways.
Includes index.
Keywords: Tourism.; Tourism -- Technological innovations.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Tourism industry.; elektronické knihy; electronic books